A pain management specialist - Santosa, Agus (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2020)
Pain management must be done systematically according to the type of pain and its severity level in order to obtain optimal results. Therefore it is necessary to have an expert in pain management, who is equipped with a variety of pain management knowledge. In Indonesia there is no specific profession or license to become a pain management specialist. In this article the author tries to explain what is pain management specialist from various references abroad.